1979
DOI: 10.1007/bf01955118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of splenectomy on the humoral immune response in the lizard,Scincus scincus

Abstract: Adult splenectomy in the lizard, Scincus scincus, did not affect humoral immune response to rat erythrocytes until 30 days post-immunization, but severely depressed subsequent antibody production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, IgM likely plays a role in mucosal responses, owing to its presence in gut mucus and its role as secretory Ig (66, 68). Splenectomy abrogates the humoral response, which demonstrates the functional importance of the spleen in immune responses in the lizard Scincus scincus (78). Notably, the spleen is subject to seasonal variation in the snake Psammophis schokari : The white pulp is involuted during summer, and winter slows the immune response (79).…”
Section: Reptilian B Cellsmentioning
confidence: 93%
“…However, IgM likely plays a role in mucosal responses, owing to its presence in gut mucus and its role as secretory Ig (66, 68). Splenectomy abrogates the humoral response, which demonstrates the functional importance of the spleen in immune responses in the lizard Scincus scincus (78). Notably, the spleen is subject to seasonal variation in the snake Psammophis schokari : The white pulp is involuted during summer, and winter slows the immune response (79).…”
Section: Reptilian B Cellsmentioning
confidence: 93%
“…Whereas, early date of sowing (late October and early November) significantly increased vegetative growth, seed yield and its quality . 6,7,8 However, each delay in sowing date beyond mid November resulted steadily reduction in growth and yield . Attia et al reported that sowing field bean in the 7,9,10 11 intermediate date (10th November) produced highest values of seed yield and its components and high seed quality traits ranked by early (20th October) then late planting dates (1st December).…”
Section: Introductionmentioning
confidence: 99%